Magnesium ion-doped nitrogen-carbon catalyst, preparation method and application of magnesium ion-doped nitrogen-carbon catalyst in transfer hydrogenation reaction of biomass unsaturated carbonyl compound

By using magnesium ion-doped nitrogen carbon catalysts, the problems of low activity and frequent side reactions in ethanol are solved, and efficient selective reduction of unsaturated carbonyl compounds of biomass are achieved, and the stability and universality of the catalyst are improved.

CN119608208APending Publication Date: 2025-03-14HUAIYIN TEACHERS COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411797908.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the transfer and hydrogenation process of existing biomass unsaturated carbonyl compounds, there are problems such as acidic sites that lead to many side reactions, high metal element content and low activity in ethanol.

Method used

A nitrogen carbon catalyst with magnesium ion doped is used. The catalyst does not contain acidic sites, has a low magnesium content, and forms a four-coordination structure with pyridine nitrogen. It is prepared through coordination self-assembly, quantitative doping and high-temperature pyrolysis processes.

Benefits of technology

The catalytic activity is significantly improved in ethanol, the occurrence of side reactions is reduced, the yield, selectivity and conversion frequency of the target product are improved, and the catalyst has excellent stability and universality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608208A_ABST
    Figure CN119608208A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium ion-doped nitrogen-carbon catalyst, a preparation method and application of the magnesium ion-doped nitrogen-carbon catalyst in a transfer hydrogenation reaction of a biomass unsaturated carbonyl compound. The catalyst is a nitrogen-doped carbon catalyst and contains magnesium, nitrogen is pyridine nitrogen, and magnesium is a single atom and forms a tetra-coordinated structure with pyridine nitrogen; in the catalyst, the content of the magnesium element is 0.1-2 wt%, and the content of the nitrogen element is 5-20 wt%. The catalyst only contains a Lewis acidic site and a Lewis alkaline site, does not contain # imgabs0 # acidic site, and can take cheap and renewable bioethanol as an in-situ hydrogen donor and a reaction solvent; various biomass unsaturated carbonyl compounds are selectively converted into corresponding high-added-value alcohol chemicals through a hydrogen free radical transfer hydrogenation reaction under mild reaction conditions, the whole reaction system is green and safe, and the target product is high in selectivity and has excellent catalytic stability and universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnesium ion-doped nitrogen-carbon catalyst, a preparation method and application thereof in a transfer hydrogenation reaction of unsaturated carbonyl compounds of biomass, and belongs to the technical field of catalyst preparation and application. Background Art

[0002] Biomass is the most abundant and renewable green carbon source in nature. Converting it into high-value-added fine chemicals is an important way to achieve sustainable development of the chemical industry. It is also a frontier field that countries around the world are competing to lay out and a hot topic in current scientific research. Biomass unsaturated carbonyl compounds (BDUCCs) are an important part of the entire biomass-based high-value-added fine chemical system. Their selective reduction products can be widely used in industries such as medicine, pesticides, food, spices, fuels and materials. Therefore, the study of the selective reduction of BDUCCs has very important scientific significance and research value. It is well known that 5-hydroxymethylfurfural, furfural, benzaldehyde and levulinic acid are typical representatives of BDUCCs, and their molecules contain multiple active chemical bonds such as carbon-oxygen double bonds (C=O), carbon-carbon double bonds (C=C), ether bonds (COC) and carboxyl bonds (O=C-OH). While the C=O in BDUCCs undergoes hydrogenation reduction reaction, side reactions such as hydrogenolysis, decarbonylation, rearrangement and ring opening may also occur. Therefore, it is crucial to develop a suitable catalytic method to ensure the preferential hydrogenation of C=O and avoid the deep hydrogenation of C=C, COC and O=C-OH as much as possible for the selective reduction of BDUCCs.

[0003] At present, the methods for selective reduction of BDUCCs mainly include traditional hydrogenation, electrochemical hydrogenation, photocatalytic hydrogenation, biocatalytic hydrogenation and MPV transfer hydrogenation. Among them, the MPV transfer hydrogenation method does not require the use of exogenous hydrogen as a hydrogen donor, and has a very high specificity for the hydrogenation of C=O, which is very beneficial for the selective reduction of BDUCCs. In the process of selectively reducing BDUCCs using the MPV transfer hydrogenation method, the core work is to design a highly efficient and selective catalyst. Regarding the design of catalysts, the research focus in recent years has been mainly on some metal organic coordination polymer catalysts, such as Zr-PN (ACS Catalysis, 2016, 6:7722-7727), Zr-CA (Chemical Engineering Journal, 2018, 352:110-119), Zr-DTMP (Journal of Energy Chemistry, 2019, 37:82-92), Zr-LS (Applied Catalysis B: Environmental, 2019, 248:31-43), Zr-TN (Green Chemistry, 2020, 22:180-186), Zr-ATMP (Molecular Catalysis, 2022, 524:112253), Hf-DTMP (Sustainable Energy Fuels, 2019, 3:1033), Hf-FDCA (Applied Catalysis B: Environmental, 2018, l 227:79-89) and Hf@CCSO3H (Catalysis Letters, 2020, 150:2038-2044), etc.

[0004] It should be noted that although metal organic coordination polymer catalysts can effectively catalyze the selective reduction of BDUCCs, these catalysts contain a certain amount of Acidic sites, and The presence of acidic sites will promote the occurrence of side reactions such as acetalization and etherification to a certain extent, thereby reducing the yield and selectivity of the target product. Moreover, the metal content in the metal organic coordination polymer catalyst is very high, and some even exceed 40%, which not only greatly increases the cost of the catalyst, but also greatly reduces the atomic utilization rate and conversion frequency of the catalyst. In addition, most metal organic coordination polymer catalysts use secondary alcohols (such as isopropanol and sec-butyl alcohol) as hydrogen donors, and the effect is extremely unsatisfactory in more inexpensive and easy-to-make primary alcohols (such as ethanol), which also largely limits the application of metal organic coordination polymers in the large-scale production of biomass-based high-value-added fine chemicals. Summary of the invention

[0005] The catalyst used in the existing biomass unsaturated carbonyl compound transfer hydrogenation process contains Acidic sites lead to many side reactions, high metal element content and low activity in ethanol. The present invention provides a magnesium ion-doped nitrogen-carbon catalyst for transfer hydrogenation of unsaturated carbonyl compounds in biomass in ethanol and a preparation method thereof. Acidic sites, where magnesium is a single atom in the catalyst structure and has a low content, have high activity in ethanol.

[0006] The technical solution adopted by the present invention is:

[0007] A magnesium ion-doped nitrogen-carbon catalyst, wherein the catalyst is a nitrogen-doped carbon catalyst and contains magnesium, the nitrogen is pyridinic nitrogen, the magnesium is a single atom and forms a four-coordinate structure with the pyridinic nitrogen;

[0008] In the catalyst, the magnesium content is 0.1-2wt%, and the nitrogen content is 5-20wt%;

[0009] Its molecular structure is Figure 8 As shown, the gray circle represents the carbon atom; magnesium acts as the Lewis acid center, pyridine nitrogen acts as the Lewis basic center, the magnesium and nitrogen are in a four-coordinate structure of Mg-N4, and there is obvious electron transfer.

[0010] The preparation method of the above-mentioned magnesium ion-doped nitrogen-carbon catalyst is to add a surfactant to a solution containing a magnesium salt, a zinc source and imidazole for reaction, and then stand, centrifuge, wash and dry to obtain a magnesium-doped ZIF material; then pyrolyze the magnesium-doped ZIF material in a nitrogen atmosphere to obtain a magnesium ion-doped nitrogen-carbon catalyst.

[0011] Preferably, the surfactant is polyvinylpyrrolidone, hexadecyltrimethylammonium bromide or Pluronic F127;

[0012] The magnesium salt is magnesium nitrate, magnesium chloride or magnesium sulfate;

[0013] The zinc source is one or both of zinc nitrate and zinc acetate;

[0014] The imidazole is one or both of 1-methylimidazole and 2-methylimidazole.

[0015] Preferably, the usage ratio of the surfactant, the magnesium salt, the zinc source and the imidazole is (1-8) g: (0.1-15) mmol: (20-60) mmol: (150-180) mmol.

[0016] Preferably, the reaction conditions are: room temperature, 5-50 hours; the standing conditions are: room temperature, 1-8 hours; and the drying conditions are: 50-100° C., 3-15 hours.

[0017] Preferably, the pyrolysis conditions are: 700-1200°C, heating rate 2-10°C / min, 1-6h.

[0018] The above-mentioned magnesium ion-doped nitrogen-carbon catalyst is used in the transfer hydrogenation reaction of unsaturated carbonyl compounds of biomass, wherein the unsaturated carbonyl compounds of biomass are furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde, benzaldehyde or cyclohexanone, and the products are furfuryl alcohol, 5-methylfurfuryl alcohol, 2,5-furan dimethanol, p-methylbenzyl alcohol, p-hydroxymethylbenzyl alcohol, benzyl alcohol or cyclohexanol.

[0019] Preferably, the application comprises the following steps: adding a magnesium ion-doped nitrogen-carbon catalyst, a biomass unsaturated carbonyl compound and an alcohol in-situ hydrogen donor into a reaction kettle, heating and stirring for reaction.

[0020] Preferably, the amount of the biomass unsaturated carbonyl compound is 1-5wt% of the amount of the alcohol in-situ hydrogen donor, and the amount of the magnesium single atom catalyst is 10-50wt% of the amount of 5-hydroxymethylfurfural;

[0021] The alcohol in-situ hydrogen donor is ethanol, n-propanol, isopropanol, n-butanol or sec-butanol.

[0022] Preferably, the reaction temperature is 120-180° C., and the reaction time is 1-12 h.

[0023] The beneficial effects of the present invention are:

[0024] Using cheap and readily available magnesium ions as dopants, polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, and Pluronic F127 as surfactants, and ZIF materials as sacrificial templates, a magnesium-nitrogen tetracoordinated single-atom catalyst (Mg-NC) was prepared through coordination self-assembly, quantitative doping, and high-temperature pyrolysis. The preparation process is simple and controllable, with extremely high specific surface area and extremely low magnesium metal content, and only contains Lewis acidic sites and Lewis basic sites, without any Acidic sites. Mg-NC can also use cheap and renewable bioethanol as an in-situ hydrogen donor and reaction solvent to selectively convert biomass unsaturated carbonyl compounds such as 5-hydroxymethylfurfural, furfural, 5-methylfurfural, benzaldehyde, p-methylbenzaldehyde and cyclohexanone into corresponding high-value-added alcohol chemicals under mild reaction conditions through hydrogen radical transfer hydrogenation. The entire reaction system is green and safe, with high selectivity for the target product and excellent catalytic stability and universality. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM image (a) and FT-IR image (b) of ZIF-8-F prepared in Comparative Example 2;

[0026] Figure 2 The SEM spectrum (a) and FT-IR spectrum (b) of NC-F prepared in Comparative Example 2;

[0027] Figure 3 The SEM image (a) and FT-IR image (b) of Mg@ZIF-8-F-1 prepared in Example 1;

[0028] Figure 4 (a) SEM image and (b) FT-IR image of Mg-NC-1 prepared in Example 1;

[0029] Figure 5 is the HAADF-STEM image of Mg-NC-1 prepared in Example 1;

[0030] Figure 6 is the XANES graph of Mg-NC-1 prepared in Example 1;

[0031] Figure 7 This is the R space simulation diagram of the EXAFS of Mg-NC-1 prepared in Example 1;

[0032] Figure 8 Schematic diagram of the tetracoordinate structure of Mg-NC-1 prepared in Example 1;

[0033] Fig. 9 XPS graphs of Mg (a) and N (b) of Mg-NC-1 prepared in Example 1;

[0034] Fig.10 is the Py-IR image of Mg-NC-1 prepared in Example 1;

[0035] Fig.11 GC chromatogram of the selective synthesis of BHMF by HMF catalyzed by Mg-NC-1 prepared in Example 1;

[0036] Fig.12 This is the GC chromatogram of the selective synthesis of furfuryl alcohol from furfural catalyzed by Mg-NC-1 prepared in Example 1. DETAILED DESCRIPTION

[0037] In this application, magnesium ions are used as dopants, Pluronic F127 is used as a surfactant, and ZIF-8 is used as a sacrificial template to prepare a magnesium-nitrogen coordinated single-atom catalyst (Mg-NC) through coordination self-assembly, quantitative doping, and high-temperature pyrolysis. The Mg in the Mg-N structure formed by magnesium and pyridine nitrogen during the high-temperature pyrolysis process2+ Can provide Lewis acid sites, N 3- Can provide Lewis basic sites and does not contain Acidic sites, their synergistic effect can significantly avoid the occurrence of side reactions such as acetalization and etherification during transfer hydrogenation, and promote the selective conversion of unsaturated carbonyl compounds in biomass into corresponding high-value-added products. More importantly, there is a four-coordinate structure between Mg and N, which is conducive to the transfer of electrons from Mg atoms to N atoms, resulting in a decrease in the electron cloud density around Mg atoms and an increase in the electron cloud density around N atoms. This can improve the adsorption performance of the catalyst for the reaction substrate, promote the generation of hydrogen radicals in ethanol, and greatly increase the catalytic activity of the MPV transfer hydrogenation reaction, thereby improving the yield, selectivity and conversion frequency of the target product.

[0038] Comparative Example 1

[0039] 40mmol zinc nitrate and 160mmol 2-methylimidazole were added to 250mL methanol, marked as solution A and solution B respectively, and stirred with ultrasound assistance until completely dissolved; solution B was added dropwise to solution A, continued to stir for 20h, and then stood at room temperature for 4h; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80℃ for 12h to obtain ZIF-8. Subsequently, ZIF-8 was placed in a tubular reactor, heated to 950℃ at a rate of 5℃ / min under a nitrogen atmosphere, and high-temperature pyrolysis for 2h to obtain ZIF-8-derived carbon nitride, abbreviated as NC.

[0040] SEM and FT-IR analysis showed that after high-temperature pyrolysis, ZIF-8 had been converted into NC, and the surface of NC became rough due to the removal of Zn and small molecular pyrolysis products in ZIF-8. In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of ​​NC was 602 m 2 / g, the content of Mg element is 0, and the content of N element is 10.3wt%.

[0041] Next, 0.2g 5-hydroxymethylfurfural (HMF), 0.1g NC and 19.8g ethanol were added to the reactor, and the temperature was raised to 140°C at a stirring speed of 400rpm. After 5h of MPV transfer hydrogenation reaction, 2,5-furan dimethanol (BHMF) was obtained. According to gas chromatography, the conversion rate of HMF was only 38.2%, and the yield and selectivity of BHMF were only 23.0% and 60.3%, respectively, which shows that N has a certain catalytic transfer hydrogenation activity as a Lewis basic site.

[0042] Comparative Example 2

[0043] 4 g Pluronic F127, 40 mmol zinc nitrate and 160 mmol 2-methylimidazole were added to 100 mL, 150 mL and 250 mL methanol, respectively, marked as solution A, solution B and solution C, and stirred under ultrasound assistance until completely dissolved; solution A was slowly added to solution B and stirred for 30 min; solution C was added dropwise to the mixed solution of A and B, and continued to stir for 20 h, and then allowed to stand at room temperature for 4 h; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80 ° C for 12 h to obtain ZIF-8-F ( Figure 1 Subsequently, ZIF-8-F was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 h, ZIF-8-F-derived carbon nitride, abbreviated as NC-F ( Figure 2 ).

[0044] SEM and FT-IR analysis showed that after high-temperature pyrolysis, ZIF-8-F had been transformed into NC-F, and the surface of NC became rougher due to the removal of Zn, surfactants and small molecular pyrolysis products in ZIF-8-F. In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of ​​NC was 670 m 2 / g, the content of Mg element is 0, and the content of N element is 11.42%.

[0045] Next, 0.2g HMF, 0.1g NC and 19.8g ethanol were added to the reactor, and the temperature was raised to 140°C at a stirring speed of 400rpm. BHMF was obtained after 5h of MPV transfer hydrogenation reaction. According to gas chromatography, the conversion rate of HMF was 49.8%, and the yield and selectivity of BHMF were 31.4% and 63.0%, respectively. This shows that the addition of surfactants can promote the pyrolysis process of ZIF-8, increase the specific surface area of ​​NC-F, and better stabilize the nitrogen element to increase its content, thereby improving the catalytic transfer hydrogenation activity of NC-F to a certain extent.

[0046] Example 1

[0047] This example is used for comparative analysis with Comparative Example 2, and the difference from Comparative Example 2 is that magnesium salt is also added when preparing ZIF-8-F.

[0048] 4 g of Pluronic F127 was added to 100 mL of methanol, 2 mmol of magnesium nitrate and 40 mmol of zinc nitrate were added to 150 mL of methanol, and 160 mmol of 2-methylimidazole was added to 250 mL of methanol, respectively, and the solutions were marked as solution A, solution B, and solution C, and stirred under ultrasound assistance until completely dissolved; solution A was slowly added to solution B and stirred for 30 min; solution C was added dropwise to the mixed solution of A and B, and continued to stir for 20 h, and then allowed to stand at room temperature for 4 h; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80 ° C for 12 h to obtain magnesium-doped Mg@ZIF-8-F-1( Figure 3 ). Subsequently, Mg@ZIF-8-F-1 was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 h, a magnesium-based single-atom catalyst derived from Mg@ZIF-8-F-1 was obtained, which is abbreviated as Mg-NC-1 ( Figure 4 ).

[0049] SEM and FT-IR analysis showed that after high-temperature pyrolysis, Mg@ZIF-8-F-1 had been transformed into Mg-NC-1, and the surface of Mg-NC-1 became rougher due to the removal of Zn, surfactants and small molecular pyrolysis products in Mg@ZIF-8-F-1. BET, ICP-AES, XPS and spherical aberration electron microscopy characterization showed that the specific surface area of ​​Mg-NC-1 was 702 m 2 / g, the content of N element is 12.85wt%, the content of Mg element is 0.37wt% and distributed in a single atomic state ( Figure 5 ). By synchrotron radiation ( Figure 6 ) Characterization analysis shows that the magnesium and nitrogen are in a four-coordinate structure ( Figure 7 ), that is, one Mg atom coordinates with four N atoms ( Figure 8 ). High-resolution XPS analysis shows that there is obvious electron transfer from Mg atoms to N atoms in Mg-NC-1 ( Fig. 9 ). Py-IR analysis shows that the Mg-NC-1 formed after high temperature pyrolysis has only Lewis acid-base sites, but no Acidic sites ( Fig.10 ).

[0050] Next, 0.2g HMF, 0.1g Mg-NC-1 and 19.8g ethanol were added to the reactor, heated to 140°C at a stirring speed of 400rpm, and MPV transfer hydrogenation reaction was performed for 5h to obtain BHMF. According to gas chromatography, the conversion rate of HMF can reach 92.6%, and the yield and selectivity of BHMF can reach 87.7% and 94.8%, respectively.

[0051] By comparing this embodiment with Comparative Example 2, it can be seen that the introduction of Mg element can not only promote the pyrolysis process of ZIF-8 and increase the specific surface area of ​​Mg-NC-1, but also form a stable coordination structure with N element, promote the transfer of electrons from Mg atoms to N atoms, thereby reducing the electron cloud density around Mg atoms and increasing the electron cloud density around N atoms, which can improve the adsorption performance of Mg-NC-1 for reaction substrates and greatly increase the catalytic activity of MPV transfer hydrogenation reaction. In other words, the catalyst Mg-NC-1 significantly improves the conversion rate of HMF, the yield and selectivity of BHMF.

[0052] Example 2

[0053] 4 g Pluronic F127 was added to 100 mL methanol, 4 mmol magnesium nitrate and 40 mmol zinc nitrate were added to 150 mL methanol, and 160 mmol 2-methylimidazole was added to 250 mL methanol, respectively marked as solution A, solution B and solution C, and stirred with ultrasound assistance until completely dissolved; solution A was slowly added to solution B and stirred for 30 min; solution C was added dropwise to the mixed solution of A and B, and continued to stir for 20 h, and then allowed to stand at room temperature for 4 h; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and magnesium-doped Mg@ZIF-8-F-2 was obtained by drying at 80 °C for 12 h. Subsequently, Mg@ZIF-8-F-2 was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 hours, a magnesium-based single-atom catalyst derived from Mg@ZIF-8-F-2, abbreviated as Mg-NC-2, was obtained.

[0054] SEM and FT-IR analysis showed that after high-temperature pyrolysis, Mg@ZIF-8-F-2 had been converted into Mg-NC-2. BET, ICP-AES, XPS and spherical aberration electron microscopy characterization showed that the specific surface area of ​​Mg-NC-2 was 425 m 2 / g, the content of N element is 10.74wt%, and the content of Mg element is 0.86wt% and distributed in a single atomic state. Synchrotron radiation characterization analysis shows that there is a four-coordinate structure between magnesium and nitrogen, that is, one Mg atom coordinates with four N atoms.

[0055] Next, 0.2g HMF, 0.1g Mg-NC-2 and 19.8g ethanol were added to the reactor, heated to 140°C at a stirring speed of 400rpm, and BHMF was obtained after 5h of MPV transfer hydrogenation reaction. According to gas chromatography, the conversion rate of HMF can reach 77.7%, and the yield and selectivity of BHMF can reach 71.6% and 92.1% respectively, which shows that there is an obvious synergistic catalytic effect between Mg and N. When the content of the two is at a suitable level, better catalytic activity can be exerted.

[0056] Example 3

[0057] 0.2g HMF, 0.1g Mg-NC-1 in Example 1 and 19.8g ethanol were added to the reactor, heated to 150°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 5h to obtain BHMF. Gas chromatography showed that the conversion rate of HMF could reach 100%, and the yield and selectivity of BHMF could reach 96.3% ( Fig.11 ), the conversion frequency (TOF) can reach 19.85h -1 This shows that Mg-NC-1 has excellent catalytic activity and is significantly better than that reported in the relevant literature (Table 1). More importantly, Mg-NC-1 was separated from the reaction solution, washed and dried, and then subjected to the next MPV transfer hydrogenation reaction under the above reaction conditions. The results showed that after Mg-NC-1 was recycled three times, the conversion rate of HMF and the yield of BHMF could still reach 98.2% and 94.8% respectively, showing good catalytic stability.

[0058] By comparing this example with Example 1, it can be seen that optimizing the reaction conditions can further enhance the catalytic activity of the catalyst.

[0059] Table 1

[0060]

[0061]

[0062] References:

[0063] [1]Green Chemistry, 2016, 18:1080-1088;

[0064] [2]Chemical Engineering Journal, 2018, 352:110-119;

[0065] [3]Sustainable Energy Fuels, 2019, 3:1033-1041;

[0066] [4]Journal of Energy Chemistry, 2019, 37:82-92;

[0067] [5]ACS Sustainable Chemistry&Engineering, 2021, 9:15557-1557;

[0068] [6]Biomass Conversion and Biorefinery, 2024, 14:2045-2061.

[0069] Example 4

[0070] This example is used for comparative analysis with Example 3, and the difference from Example 3 is that furfural is used as a substrate.

[0071] 0.15 g furfural (the molar amount is the same as HMF), 0.1 g Mg-NC-1 in Example 1 and 19.85 g ethanol were added to the reactor, and the temperature was raised to 150°C at a stirring speed of 400 rpm. Furfuryl alcohol was obtained after 5 hours of MPV transfer hydrogenation reaction. The gas chromatograph showed that the conversion rate of furfural was 62.9%, and the yield and selectivity of furfuryl alcohol were 55.5% and 88.2% respectively. Fig.12 ), the conversion frequency (TOF) is 11.39h -1 This result is much lower than that of HMF, which indicates that the MPV transfer hydrogenation process mediated by Mg-NC-1 is not the traditional "six-membered ring intermediate reaction mechanism", because in the "six-membered ring intermediate reaction mechanism", the strong steric hindrance caused by the lack of hydroxymethyl group in furfural will lead to its catalytic effect being higher than that of HMF.

[0072] Example 5

[0073] 0.2g HMF, 0.1g Mg-NC-1 in Example 1, 0.02g Na2CO3 and 19.8g ethanol were added to the reactor, heated to 150°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 5h to obtain BHMF. Gas chromatography showed that the conversion rate of HMF was 32.4%, the yield and selectivity of BHMF were 14.1% and 43.5% respectively, and the conversion frequency (TOF) could reach 2.91h. -1This shows that the MPV transfer hydrogenation process mediated by Mg-NC-1 can be obviously inhibited by Na2CO3, because Na2CO3 as a base can neutralize the hydrogen radicals from ethanol in the reaction system. In other words, the MPV transfer hydrogenation process mediated by Mg-NC-1 is carried out through the "hydrogen radical reaction mechanism", and in the "hydrogen radical reaction mechanism", the hydroxymethyl group on HMF not only does not have the effect of steric hindrance, but also helps the catalyst to adsorb the substrate and improve the catalytic activity of the catalyst, which is also the reason why the catalytic effect of Example 3 is better than that of Example 4.

[0074] Example 6

[0075] 0.15g furfural (the molar amount is consistent with HMF), 0.1g Mg-NC-1 in Example 1 and 19.85g ethanol are added to the reactor, and the temperature is raised to 170°C at a stirring speed of 400rpm. Furfuryl alcohol can be obtained after 7h of MPV transfer hydrogenation reaction. According to gas chromatography detection, the conversion rate of furfural is 99.3%, the yield and selectivity of furfuryl alcohol are 94.8% and 95.5% respectively, and the conversion frequency (TOF) is 13.73h -1 This indicates that increasing the reaction temperature and extending the reaction time can enhance the catalytic effect of Mg-NC-1 on furfural.

[0076] In order to better highlight the effectiveness of Mg-NC-1 prepared in Example 1, the catalytic effect of Mg-NC-1 on HMF was studied using n-propanol, isopropanol, n-butanol and sec-butanol as in situ hydrogen donors, wherein the catalytic reaction conditions were adaptively adjusted accordingly due to the applicable range of the hydrogen donor itself. The specific results are shown in Examples 7-10.

[0077] Example 7

[0078] 0.2g HMF, 0.1g Mg-NC-1 in Example 1 and 19.8g n-propanol were added to the reactor, heated to 150°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 6h to obtain BHMF. Gas chromatography showed that the conversion rate of HMF was 100%, the yield and selectivity of BHMF were 97.1% respectively, and the conversion frequency (TOF) was 16.66h. -1 .

[0079] Example 8

[0080] 0.2g HMF, 0.1g Mg-NC-1 in Example 1 and 19.8g isopropanol were added to the reactor, heated to 150°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 3h to obtain BHMF. Gas chromatography showed that the conversion rate of HMF was 100%, the yield and selectivity of BHMF were 99.5% respectively, and the conversion frequency (TOF) was 34.15h. -1 .

[0081] Example 9

[0082] 0.2g HMF, 0.1g Mg-NC-1 in Example 1 and 19.8g n-butanol were added to the reactor, heated to 150°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 7h to obtain BHMF. Gas chromatography showed that the conversion rate of HMF was 100%, the yield and selectivity of BHMF were 96.8% respectively, and the conversion frequency (TOF) was 14.24hh. -1 .

[0083] Example 10

[0084] 0.2g HMF, 0.1g Mg-NC-1 in Example 1 and 19.8g sec-butyl alcohol were added to the reactor, heated to 150°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 5h to obtain BHMF. Gas chromatography showed that the conversion rate of HMF was 100%, the yield and selectivity of BHMF were 95.4% respectively, and the conversion frequency (TOF) was 19.64h. -1 .

[0085] It can be seen from Examples 7-10 that Mg-NC-1 can efficiently catalyze HMF to produce BHMF through the MPV transfer hydrogenation process in different alcohols, demonstrating excellent universality as an alcohol hydrogen donor.

[0086] In order to further demonstrate the effectiveness of Mg-NC-1 in Example 1, the substrate universality of Mg-NC-1 was studied using biomass unsaturated carbonyl compounds such as 5-methylfurfural, benzaldehyde, p-methylbenzaldehyde, cyclohexanone and levulinic acid as substrates, wherein the catalytic reaction conditions were adaptively adjusted accordingly according to the applicable scope of the substrate itself. The specific results are shown in Table 2 (Examples 11-15).

[0087] Table 2

[0088]

[0089] As can be seen from Table 2, Mg-NC-1 can not only efficiently catalyze the selective conversion of HMF into BHMF in ethanol, but also effectively catalyze the conversion of biomass unsaturated carbonyl compounds such as 5-methylfurfural, benzaldehyde, p-methylbenzaldehyde, cyclohexanone and levulinic acid into corresponding high value-added products, which further illustrates that Mg-NC-1 has excellent catalytic activity and substrate universality.

[0090] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A magnesium ion-doped nitrogen-carbon catalyst, characterized in that: The catalyst is a nitrogen-doped carbon catalyst and contains magnesium, the nitrogen is pyridinic nitrogen, the magnesium is a single atom and forms a four-coordinate structure with the pyridinic nitrogen; In the catalyst, the magnesium content is 0.1-2wt%, and the nitrogen content is 5-20wt%.

2. The method for preparing the magnesium ion-doped nitrogen-carbon catalyst according to claim 1, characterized in that: The method comprises adding a surfactant into a solution containing a magnesium salt, a zinc source and imidazole to react, and then standing, centrifuging, washing and drying to obtain a magnesium-doped ZIF material; and then pyrolyzing the magnesium-doped ZIF material in a nitrogen atmosphere to obtain a magnesium ion-doped nitrogen-carbon catalyst.

3. The method for preparing the magnesium ion-doped nitrogen-carbon catalyst according to claim 2, characterized in that: The surfactant is polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide or Pluronic F127; The magnesium salt is magnesium nitrate, magnesium chloride or magnesium sulfate; The zinc source is one or both of zinc nitrate and zinc acetate; The imidazole is one or both of 1-methylimidazole and 2-methylimidazole.

4. The method for preparing the magnesium ion-doped nitrogen-carbon catalyst according to claim 2, characterized in that: The dosage ratio of the surfactant, magnesium salt, zinc source and imidazole is (1-8) g: (0.1-15) mmol: (20-60) mmol: (150-180) mmol.

5. The method for preparing the magnesium ion-doped nitrogen-carbon catalyst according to claim 2, characterized in that: The reaction conditions are: room temperature, 5-50h; the standing conditions are: room temperature, 1-8h; the drying conditions are: 50-100°C, 3-15h.

6. The method for preparing the magnesium ion-doped nitrogen-carbon catalyst according to claim 2, characterized in that: The pyrolysis conditions are: 700-1200°C, heating rate 2-10°C / min, 1-6h.

7. The use of the magnesium ion-doped nitrogen-carbon catalyst according to claim 1 in the transfer hydrogenation reaction of unsaturated carbonyl compounds in biomass, characterized in that: The unsaturated carbonyl compounds of biomass are furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde, benzaldehyde or cyclohexanone, and the products are furfuryl alcohol, 5-methylfurfuryl alcohol, 2,5-furan dimethanol, p-methylbenzyl alcohol, p-hydroxymethylbenzyl alcohol, benzyl alcohol or cyclohexanol.

8. The use according to claim 7, characterized in that: The application comprises the following steps: adding a magnesium ion-doped nitrogen-carbon catalyst, a biomass unsaturated carbonyl compound and an alcohol in-situ hydrogen donor into a reaction kettle for heating and stirring for reaction.

9. The use according to claim 8, characterized in that: The amount of biomass unsaturated carbonyl compound used is 1-5wt% of the amount of alcohol in-situ hydrogen donor used, and the amount of magnesium single atom catalyst used is 10-50wt% of the amount of 5-hydroxymethylfurfural used; The alcohol in-situ hydrogen donor is ethanol, n-propanol, isopropanol, n-butanol or sec-butanol.

10. The use according to claim 8, characterized in that: The reaction temperature is 120-180°C and the reaction time is 1-12h.